Incidence, National Trend, and Outcome of Nontraumatic Subarachnoid Haemorrhage in Taiwan: Initial Lower Mortality, Poor Long-Term Outcome. (31st March 2014) - Lin, Hsing-Lin; Soo, Kwan-Ming; Chen, Chao-Wen; Lin, Yen-Ko; Lin, Tsung-Ying; Kuo, Liang-Chi; Lee, Wei-Che; Huang, Shiuh-Lin
Abstract : To investigate the longitudinal trend of nontraumatic subarachnoid haemorrhage (SAH), we analyzed the annual population-based incidence and mortality rate of nontraumatic subarachnoid hemorrhage in Taiwan. Logistic regression was used to identify independent predictors of mortality. The average incidence rate (IR) of nontraumatic SAH was 6.25 ± 0.88 per 100, 000 per year. The prevalence of female patients was higher than in the male population (54.5% versus 45.5%). The average age of these patients was 55.78 ± 17.09 and females were older than males (58.50 ± 15.9 versus 52.45 ± 18.50, P < 0.001 ). Of these patients, 97.6% (611/626) were treated with surgical intervention with clipping procedure and 2.9% (18/626) with coiling. Total mortality of these patients was 13.4% (84/626). In adjusted analysis, age (odds ratio [OR], 0.97; 95% confidence interval [CI], 0.98-0.98; P < 0.001 ) and Charlson comorbidity index (OR, 0.709; 95% CI, 0.57–0.88; P = 0.002 ) remained independent predictors of the mortality. Patients with nontraumatic SAH had a much higher prevalence in older age groups and in females than in the general population. Patients with old age and more comorbidity have higher mortality. Aggressive management of patients might reduce the initial mortality; however, patient outcome still remains poor.